Impact of Boycott Action on Financial Performance and Market Reaction - Siregar, Ira Sovia; Fachrezi, Farraz Nabila; Sulistyowati, Wiwit Apit (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Boycott is widely recognized as a form of public protest related to the Israel–Palestine conflict, manifested through consumers’ decisions to refrain from purchasing or using products affiliated with pro‑Israel entities. This research seeks to examine the differences in companies performance in Indonesia before and during the boycott period by employing a quantitative research design. The study population comprises 268 companies listed on the Indonesia Stock Exchange from 2020-2023, with purposive sampling applied to select relevant firms. Data were processed using descriptive statistical analysis to capture shifts in key financial indicators. The findings indicate that performance measures such as ROE, ROA, CR, DAR, and DER experienced a notable decline, which in turn influenced stock prices and Trading Volume Activity. In contrast, company size remained relatively stable throughout the observed period. These declines illustrate a negative market reaction, reflecting reduced investor confidence and diminished market enthusiasm toward companies perceived to be linked with boycott‑affected products.